Hidrólise de resíduos lignocelulósicos utilizando extrato enzimático celulolítico produzido por Trichoderma reesei atcc 2768 - Ribeiro, Josefa Angela Batista (2010)
Cellulolytic enzymatic broth by Trichoderma reesei ATCC 2768 cultived in shaker using cashew apple bagasse and coconut shell bagasse, as substrate for fermentation, was used to investigate the enzymatic hydrolysis of these substrates after pre-treatment with 1 M NaOH, wet-oxidation as well as a combination of these treatments. Hydrolysis runs were carried at 125 rpm, 50ºC and initial pH of 4.8 for 108 hours. Enzymatic broth produced using cashew apple bagasse treated with 1M NaOH (1.337 UI/mL CMCase and 0.074 UI/mL FPase), showed after the hydrolysis an initial of 0.094 g of reducing sugar/g of substrate.h with 96% yield of total reducing sugars while for the coconut shell bagasse treated using the alkaline process (0.640 UI/mL CMCase and 0.070 UI/mL FPase) exhibited an initial hydrolysis velocity of 0.025 g of reducing sugar/g of substrate.h with 48% yield of total reducing sugars. For the treatment with wet-oxidation using cashew apple bagasse as substrate enzymatic broth (0.547 UI/mL CMCase) exhibited an initial hydrolysis velocity of 0.014 g of reducing sugars/g of substrate.h with a lower yield about 89% of total reducing sugars compared to the alkaline treatment. Enzymatic broth produced using coconut shell treated by wet-oxidation showed an initial hydrolysis velocity of 0.029 g of reducing sugar/g of substrate.h with 91% yield. However, when the combination of these two treatments were used it was obtained an enzymatic broth of 1.154 UI/mL CMCase and 0.107 FPase for the cashew apple bagasse as well as 0.538 UI/mL CMCase and 0,013 UI/mL de FPase for the coconut shell bagasse. After hydrolysis, initial velocity was 0.029 g of reducing sugar/g of substrate.h. with 94% yield for the cashew apple bagasse and 0.018 g de reducing sugar/g of substrate.h with 69% yield for coconut shell bagasse. Preliminary treatment improves residues digestibility showing good yields after hydrolysis. In this case, cellulose from the residue can be converted into glucose by cellulolytic enzymes that can be used for ethanol production